Analisis Pengaruh CAR dan FDR terhadap Equivalent Rate Deposito serta Dampaknya terhadap Total Aset pada Industri Perbankan Syariah di Indonesia Periode Januari 2013 – April 2018 dengan Path Analysis - Argya Kirana Hasanah Raharyan; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the influence of CAR and FDR on Deposit Equivalent Rate which then re-analyzed its impact on Total Asset at Sharia Commercial Bank and Sharia Business Unit in Indonesia. This study used Path Analysis with quantitative approach. Statistical tool used in this research is SPSS Version 23. The data used in this research are secondary data which fully downloaded from official site of Otoritas Jasa Keuangan (OJK). The result of Regression Model 1 reveal CAR and FDR simultaneously have significant influence to Deposit Equivalent Rate, evidenced by significance value below alpha of 0,05. While the other result (Regression Model 2) show that CAR, FDR, and Deposit Equivalent Rate simultaneously have significant affect to Total Asset, which is also evidenced by significance value below alpha of 0,05.Keywords: : CAR, FDR, Equivalent Rate, Total Asset, Sharia BanksREFERENCES Algoud, Latifa M. dan Lewis, Mervyn K. 2003. Perbankan Syariah : Prinsip, Praktik, dan Prospek. Diterjemahkan Oleh : Burhan Wirasubrata. Jakarta : Serambi.  Djuwita, D., & Muhammad, A. F. 2016. Pengaruh Total DPK, FDR, NPF dan ROA terhadap Total Asset Bank Syariah di Indonesia. Jurnal Kajian Ekonomi Dan Perbankan Syari’ah, 281–297.Farook, S., Hassan, M. K., & Clinch, G. 2012. Profit Distribution Management by Islamic Banks : An Empirical Investigation. Quarterly Review of Economics and Finance, 52(3), 333– 347. Ismail. 2010. Akuntansi Bank : Teori dan Aplikasi dalam Rupiah. Jakarta : Prenada Media Group. _____. 2011. Perbankan Syariah. Jakarta : Prenada Media Group. Karim, Adiwarman. 2014. Bank Islam Analisis Fiqh dan Keuangan. Edisi Kelima. Jakarta : PT RajaGrafindo Persada. Kasmir. 2009. Bank dan Lembaga Keuanga Lainnya. Jakarta : PT RajaGrafindo Persada. ______. 2010. Dasar-Dasar Perbankan. Jakarta : PT RajaGrafindo Persada. ______. 2016. Analisis Laporan Keuangan. Jakarta : PT RajaGrafindo Persada. Lahrech, N., Lahrech, A., & Boulaksil, Y. 2014. Transparency and Performance in Islamic Banking: Implications on Profit Distribution. International Journal of Islamic and Middle Eastern Finance and Management, 7(1), 61– 88. Machmud, A., & Rukmana. 2010. Bank Syariah : Teori, Kebijakan, dan Studi Empiris di Indonesia. Jakarta: Erlangga. Masruroh, Fitriani dan Rohman Effendi. Analysis The Profit Distribution Management (PDM) Sharia Bank in Indonesia Period 2010-2014. 2016. Artikel Ilmiah Mahasiswa 2016.Muhammad. 2014. Manajemen Keuangan Syariah (1st ed.). Yogyakarta: UPP STIM YKPN. Murni, Asfia. 2009. Ekonomika Makro. Bandung : PT Refika Aditama. Mursid, A., & Suhartono, E. 2014. Faktor Determinan Nasabah dalam Pemilihan Bank Syariah. Jurnal Dinamika Manajemen, 5(4), 45–58. Oktaviana, Ulfi Kartika. 2012. Financial Ratio to Distinguish Banks, Islamic Business Units and Conventional Banks in Indonesia. Jakarta : Kementrian Agama RI Direktorat Jenderal Pendidikan Islam. Riduwan dan Kuncoro, Engkos. 2012. Cara Menggunakan dan Memaknai Path Analysis (Analisis Jalur). Bandung : Alfabeta. Rosyidi, Suherman. 2014. Pengantar Teori Ekonomi : Pendekatan Kepada Teori Ekonomi Mikro dan Makro. Edisi Revisi. Jakarta : PT RajaGrafindo Persada.  Suharso, Puguh. 2009. Metode Penelitian Kuantitatif untuk Bisnis : Pendekatan Filosofis dan Praktis. Jakarta : Indeks. Sujarweni, V. Wiratna. 2015. Metodologi Penelitian Bisnis dan Ekonomi. Yogyakarta : PUSTAKABARUPRESS. Susanti, V. 2015. Pengaruh Equivalent Rate dan Tingkat Keuntungan Terhadap Dana Pihak Ketiga (DPK) Perbankan Syariah di Indonesia. I Finance, Vol. 1. No(Juli 2015), 20. Syafrida, I., & Abror, A. 2011. Faktor-Faktor Internal Dan Eksternal Yang Mempengaruhi Pertumbuhan Aset Perbankan Syariah Di Indonesia. Juni, 10(2011), 25–33.Wahyu, D. R. (2016). Financing to Deposit Ratio (FDR) Sebagai Salah Satu Penilaian Kesehatan Bank Umum Syariah (Studi Kasus Pada Bank BJB Syariah Cabang Serang). Jurnal Ekonomi Keuangan Dan Bisnis Islam, 7(1), 19–36. http://www.bi.go.id/ diakses pada 18 Maret 2018 http://www.bps.go.id/ diakses pada 10 Mei  2018 http://www.ojk.go.id/ diakses pada 15 Mei 2018 http://republika.com/ diakses 25 Juni 2018